Oltre la “casa dell’Essere” - Ghilardi, Marcello (Scenari, 2021)
While Heidegger claims that “languge is the house of Being”, we have anyway to wonder whether this claim can be understood as something universal (or likely universal). The practices of word and writing in East-asian countries and traditions can be considered “houses” of something else, different from Being: the study of metaphoric dimension in some Chinese and Japanese poems can give some hints in order to show a difference inside affinities, and a proximity even where diversity and incompatibility seemed to rule.